Analyzing course affecting the results of inferential statistics students in UiTM Seremban using Association Rule Mining / Jaida Najihah Jamidin ... [et al.] - Jamidin, Jaida Najihah (Unit Penerbitan UiTM Kelantan, 2021)
Inferential Statistics was recognized as a high failure rate statistics course taken by the students of Bachelor of Science (Hons.) Statistics. Inferential Statistics is the most challenging course compared to the other courses since a majority of the students failed this course. This study aimed to analyze the courses affecting the result of Inferential Statistics. An Association Rule Mining was used to 126 graduated students from matriculation and foundation. Results showed that 239 rules had been obtained during the process of association rule mining. After removing the redundancy, only 106 most appropriate rules are associated with the objectives. This study focused on providing an effective mechanism for lecturers to improve students’ performance in the high failure rate of statistics courses. The university administration needs to improve the teaching and learning method to produce good academic performance.